2004
DOI: 10.1080/02786820490250836
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Aerosols from the World Trade Center Collapse Site, New York, October 2 to October 30, 2001

Abstract: The collapse of the World Trade Center (WTC) buildings #2 (South Tower), #1 (North Tower), and #7 created an enormous collapse pile which emitted intense plumes of acrid smoke and dust until roughly mid-December, when the last spontaneous surface fire occurred. We collected particles by size (8 modes, ≈12 to 0.09 micrometers diameter) and time (typical resolution of 1 to 3 h) from October 2 until late December at the EML 201 Varick Street site roughly 1.8 km NNE of the collapse site and 50 m above ground level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Only few types of cascade impactors exist for this task, for example the rotating drum impactor with 3 or 8 stages (3DRUM / 8DRUM, see Cahill, C. 2003;Cahill, T. et al 2003Cahill, T. et al , 2004Cliff et al 2003;Han et al 2005;Perry et al 2004;VanCuren et al 2005), or the streaker sampler with 3 size ranges (D'Alessandro et al 2003(D'Alessandro et al , 2004. A rotating drum impactor is characterized by one rectangular nozzle for every impactor stage and rotating wheels instead of conventional impaction plates.…”
Section: Introductionmentioning
confidence: 99%
“…Only few types of cascade impactors exist for this task, for example the rotating drum impactor with 3 or 8 stages (3DRUM / 8DRUM, see Cahill, C. 2003;Cahill, T. et al 2003Cahill, T. et al , 2004Cliff et al 2003;Han et al 2005;Perry et al 2004;VanCuren et al 2005), or the streaker sampler with 3 size ranges (D'Alessandro et al 2003(D'Alessandro et al , 2004. A rotating drum impactor is characterized by one rectangular nozzle for every impactor stage and rotating wheels instead of conventional impaction plates.…”
Section: Introductionmentioning
confidence: 99%
“…However, some respond- Table 2 Asthma and lower respiratory symptoms (N, %) among exposed (n = 578) and non-exposed (n = 702) participants, WTC asthma study, NYS, 2003 WTC World Trade Center, NYS New York State a Symptoms experienced in the absence of a respiratory infection b 5 exposed and 10 non-exposed participants did not answer this question Exposed Non-exposed p value ( 2 test) Table 3 Lower respiratory symptoms among exposed versus non-exposed participants with no previous diagnosis of asthma, by mean exposure algorithm score, WTC asthma study, NYS, 2003 Symptoms experienced in the absence of a respiratory infection WTC World Trade Center, NYS New York State, POR prevalence odds ratio, CI conWdence interval a 22 participants were excluded from these analyses for lack of exposure algorithm scores b Model is adjusted for race, ethnicity, smoking, education, a history of allergy or eczema, a family history of asthma, and report of any psychological symptom Cahill et al (2004) reported that, under certain meteorological conditions, the plumes could ventilate to the ground, leading to periods of sharply elevated coarse, Wne, and very Wne particulate mass over periods of hours 1.8 km from the collapse site and beyond. They also stated that a person could, in a few hours, be subject to materials in amounts and composition they would not have to endure in years of typical ambient conditions (Cahill et al 2004). Thus, although most of our population was not on-site during the initial days after the attack, it is likely that some NYS responders endured signiWcant intermittent exposures to dust and smoke, both on the debris pile and in surrounding areas.…”
Section: Discussionmentioning
confidence: 99%
“…They experienced a variety of potential exposures (Cahill et al 2004;JeVery et al 2003;Lioy et al 2002;McGee et al 2003;McKinney et al 2002;OVenberg et al 2004, Tao et al 2008. WTC-related dust has been described as caustic and alkaline Landrigan et al 2004), which could be irritating to the mucous membranes and the respiratory tract.…”
Section: Introductionmentioning
confidence: 97%
“…Silicon dominates all other elements, unlike the coarse mode aerosols… (Cahill et al 2004) other crustal elements (Al, Ca, and iron) seen so abundantly in the coarser particles are essentially absent in this very fine mode. (Cahill 2003) In July of 2002, Cahill reported that (emphasis added)…”
Section: Aerosol Measurements After 9/11mentioning
confidence: 94%
“…The only fuel oil source suggested by Cahill and his team was under WTC building 7, across the street from the towers (Cahill et al 2004). But it should be noted that government investigators have suggested that the fuel oil in question was burned to create the fires that caused WTC building 7 to collapse.…”
Section: Aerosol Measurements After 9/11mentioning
confidence: 98%